A influência das informações contábeis e das finanças comportamentais no mercado acionário - Giaccheri, Daniel (2010)
The paper focuses on understanding the influence of behavioral finance and accounting information on the Brazilian stock market, as its evolution, main characteristics and applications. The goal is to bring out this new subject, as discussed internationally, but with the impacts in Brazil. Event study models and parametric and nonparametric statistics were used as methodologies in seeking to measure the impact of accounting information disclosed; specifically earnings per share (EPS) reported quarterly, in the behavior of stock prices. The empirical results show that economic agents may not be represented only by taking into account the neoclassical assumptions of unlimited rationality, maximization of expected utility and risk aversion. This finding demonstrates that the agents make decisions with limited rationality, contrary to the behavior predicted by the Modern Theory of Finance and the Efficient Markets Hypothesis (EMH) and reinforce the importance of behavioral finance. The discussion of this issue is still far from resolved, the studies about it continually grows in the academic circles , however there are already many studies to deepen the integration of these two theoretical lines, modern finance theory and behavioral finance, which at the same time, may be considered controversial and also complementary